Metal-organic framework-based aptamer sensors for early diagnosis of breast cancer - Xiaoxia Yao; Wei Chen; Chi Zhang; Weixuan Shao; Mohammadreza Shokouhimehr; Can Guo; Zhengchun Liu (Sensing and Bio-Sensing Research)
Breast cancer is among the most common neoplasms in women worldwide, and timely detection is important to ensure the greatest chance of survival. Metal-organic frameworks (MOFs) possess specific advantages for application in biosensors because they possess a high specific surface area, tunable pore structure, and excellent biocompatibility. This paper summarizes the research progress of MOF-based aptamer sensors for the early detection of biomarkers of breast cancer, including progress in single-biomarker and multiplex sensing and the use of various detection methods in aptamer-based sensors. Furthermore, it discusses novel component design, optimization of detection methods, and the expansion of clinical applications with MOF-based aptamer sensors. Functionalization and adjustment of MOFs through the introduction of new aptamers and techniques have improved sensor efficiency and provided new paths for early cancer diagnosis. Despite advancements, sensitivity, selectivity, and clinical feasibility concerns are areas that require more efforts.